Functional Supramolecular Architectures of Dipyrrin Complexes - Matsuoka, Ryota; Nabeshima, Tatsuya (Frontiers in Chemistry, 2018)
Dynamic formation of self-assemblies from molecular components is a useful and efficient way to produce molecular and supramolecular architectures with sophisticated functions. The labile coordination bond and dynamic covalent bond formation as a reversible bond have often been used to create a well-organized supramolecular self-assembly. In order to realize sophisticated novel functions of the supramolecular self-assemblies, dipyrrin complexes have recently been employed as a functional unit and incorporated into the supramolecular architectures because of their outstanding properties and functions such as a high photostability and strong light absorption/emission. This review article summarizes recent development in functional supramolecular architectures of the dipyrrin complexes produced by coordination to a metal ion and dynamic covalent bond formation. Senction 1 describes the synthesis and unique functions of a series of discrete supramolecular architectures: helicates, macrocycles, and cages. In section 2, the polymeric supramolecular self-assemblies with 1D, 2D, and 3D structures are then introduced as functional infinite supramolecular architectures.